2004
DOI: 10.1007/s00421-004-1110-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyographic and electromyographic time and frequency domain responses during submaximal to maximal isokinetic muscle actions of the biceps brachii

Abstract: The purpose of this investigation was to determine the mechanomyographic (MMG) and electromyographic (EMG) amplitude and mean power frequency (MPF) versus torque relationships during isokinetic muscle actions of the biceps brachii. Twelve adults [mean (SD) age, 22.2 (2.7) years] performed submaximal to maximal isokinetic muscle actions of the dominant forearm flexors. Following determination of isokinetic peak torque (PT), the subjects randomly performed submaximal muscle actions in 20% increments from 20% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
73
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 43 publications
9
73
3
Order By: Relevance
“…In the present study, MMG IMF increased up to Ϸ50% MVC, then plateaued to 90% MVC (Fig. 3), which was consistent with the findings of Coburn et al 8 and Beck et al 4 With further validation, it is possible that the frequency domain of the MMG signal may be useful as a noninvasive tool to estimate the global firing rate of active muscles during isometric ramp contractions. The subtle differences among the findings of our study and those of Beck et al 4 and Coburn et al 8 may be related to differences between isometric step and ramp contractions.…”
Section: Maximal Voluntary Contractionssupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, MMG IMF increased up to Ϸ50% MVC, then plateaued to 90% MVC (Fig. 3), which was consistent with the findings of Coburn et al 8 and Beck et al 4 With further validation, it is possible that the frequency domain of the MMG signal may be useful as a noninvasive tool to estimate the global firing rate of active muscles during isometric ramp contractions. The subtle differences among the findings of our study and those of Beck et al 4 and Coburn et al 8 may be related to differences between isometric step and ramp contractions.…”
Section: Maximal Voluntary Contractionssupporting
confidence: 93%
“…These findings were attributed to the shift in contributions to force production from motor unit recruitment to rate coding from 60%-80% MVC. Indeed, previous studies from our laboratory have reported similar increases in MMG center frequency during isometric step 4 and ramp 37 contractions. Coburn et al 8 demonstrated a nonsignificant increase in MMG center frequency with increasing isometric force production for the vastus medialis muscle, while Beck et al 4 reported significant increases in MMG center frequency for the biceps brachii muscle during submaximal to maximal isometric step contractions.…”
Section: Maximal Voluntary Contractionssupporting
confidence: 67%
See 2 more Smart Citations
“…In the field of biomedical engineering, muscle activation and articulation have been exploited to control prosthetic limb systems [Saridis and Gootee 1982;Silva et al 2005;Castellini and van der Smagt 2009;Farina et al 2014]. Because muscle sensing provides insights not only on volitional control but also on sensorimotor control strategies, it has been applied to the monitoring of muscle fatigue [Barry et al 1992;Tarata 2003], the evaluation of muscle functions and responses to stimuli [Beck et al 2004;Kuriki and Azevedo 2012] and neurophysiological assessment [Orizio et al 1992;Orizio et al 1997].…”
Section: Introductionmentioning
confidence: 99%